2013
DOI: 10.1186/1471-2458-13-337
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status among Burmese adolescent students living in boarding houses in Thailand: a cross-sectional study

Abstract: BackgroundIn Tak province of Thailand, a number of adolescent students who migrated from Burma have resided in the boarding houses of migrant schools. This study investigated mental health status and its relationship with perceived social support among such students.MethodsThis cross-sectional study surveyed 428 students, aged 12–18 years, who lived in boarding houses. The Hopkins Symptom Checklist (HSCL)-37 A, Stressful Life Events (SLE) and Reactions of Adolescents to Traumatic Stress (RATS) questionnaires w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 53 publications
3
27
1
2
Order By: Relevance
“…This result is consistent with the findings of higher rates of depression and anxiety among Burmese adolescents students exposed to psycho-trauma in Thailand (14). This is despite male participants having been exposed to more psycho-trauma overall compared with females.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is consistent with the findings of higher rates of depression and anxiety among Burmese adolescents students exposed to psycho-trauma in Thailand (14). This is despite male participants having been exposed to more psycho-trauma overall compared with females.…”
Section: Discussionsupporting
confidence: 92%
“…The HSCL used for this study may have picked more distress in females solely because females were more likely to express distressing feelings than males (23). Reports of sexual harassments and been forced to have sex were by male children/adolescent IDPs; this is similar to the findings among traumatized Burmese adolescent where males reported more sexual harassment/abuse (14). This finding could be an under reporting or total lack of reporting (as in this case) of sexual assault by females due to the culturally sensitive nature of disclosing sexual harassment in Northern Nigeria.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, recent research demonstrated that social ties reduced depression symptoms following the disasters of the 1999 Chi-Chi earthquake in Taiwan [17] and the 2001 terrorist attacks in New York City [18] . In contrast, Akiyama et al showed that perceived social ties did not significantly affect the prevalence of depression or anxiety among Burmese refugee students living in boarding houses in Thailand [19] . To date, information on the social contexts of resident survivors after a tsunami has been scant, and how social ties affect the mental health of these individuals when vital community links have been severely devastated remains largely unknown.…”
Section: Introductionmentioning
confidence: 90%